Magnetic Activity Cycles in the Exoplanet Host Star ǫ Eridani - Metcalfe, T. S. (2013)
The active K2 dwarf ǫ Eri has been extensively characterized, both as a young solar analog and more recently as an exoplanet host star. As one of the nearest and brightest stars in the sky, it provides an unparalleled opportunity to constrain stellar dynamo theory beyond the Sun. We confirm and document the 3 year magnetic activity cycle in ǫ Eri originally reported by Hatzes and coworkers, and we examine the archival data from previous observations spanning 45 years. The data show coexisting 3 year and 13 year periods leading into a broad activity minimum that resembles a Maunder minimum-like state, followed by the resurgence of a coherent 3 year cycle. The nearly continuous activity record suggests the imultaneous operation of two stellar dynamos with cycle periods of 2.95 ± 0.03 years and 12.7 ± 0.3 years, which by analogy with the solar case suggests a revised identification of the dynamo mechanisms that are responsible for the so-called “active” and “inactive” sequences as proposed by Böhm-Vitense. Finally, based on the observed properties of ǫ Eri we argue that the rotational history of the Sun is what makes it an outlier in the context of magnetic cycles observed in other stars (as also suggested by its Li depletion), and that a Jovian-mass companion cannot be the universal explanation for the solar peculiarities.